Handbook of Biomaterial Properties - Murphy, William; Black, Jonathan; Hastings, Garth (Springer New York : Imprint: Springer, 2016)
This book provides tabular and text data relating to normal and diseased tissue materials and materials used in medical devices. Comprehensive and practical for students, researchers, engineers, and practicing physicians who use implants, this book considers the materials aspects of both implantable materials and natural tissues and fluids. Examples of materials and topics covered include titanium, elastomers, degradable biomaterials, composites, scaffold materials for tissue engineering, dental implants, sterilization effects on material properties, metallic alloys, and much more. Each chapter author considers the intrinsic and interactive properties of biomaterials, as well as their appropriate applications and historical contexts. Now in an updated second edition, this book also contains two new chapters on the cornea and on vocal folds, as well as updated insights, data, and citations for several chapters.